1979
DOI: 10.1103/physreva.20.1511
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of the3pSo4atomic-nitrogen state in a low-pressure nitrogen glow discharge

Abstract: A laser perturbation method is used to determine the relaxation rate of the 3p 'S' state of atomic nitrogen as function of pressure and current intensity in a glow discharge. Quenching is due to spontaneous radiative transitions towards lower levels and to inelastic collisions with N2 in the vibrationally excited ground state with a thermally averaged cross section of about 7.5)&10 ' cm'. Measurements allow the determination of the dissociation rate as a function of electronic temperature in the range 1-3 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…Note that in Eq. Similar conclusions were reported by Levanton et al 40 for the 3s 4 P and 2p 4 P levels 41 reported efficient quenching of the 3p 4 S 0 state by N 2 ͑X , ജ 2͒ ͑k N q = 6.5ϫ 10 −9 cm 3 s −1 ͒. Assuming a Maxwellian eedf, Czerwiec et al 12 calculated the rate coefficients for the first three processes and found that excitation from metastable states and dissociative excitation is one to two orders of magnitude smaller than excitation rates from the ground state for electron temperatures larger than 2 eV.…”
Section: A Atomic Line Intensitysupporting
confidence: 90%
“…Note that in Eq. Similar conclusions were reported by Levanton et al 40 for the 3s 4 P and 2p 4 P levels 41 reported efficient quenching of the 3p 4 S 0 state by N 2 ͑X , ജ 2͒ ͑k N q = 6.5ϫ 10 −9 cm 3 s −1 ͒. Assuming a Maxwellian eedf, Czerwiec et al 12 calculated the rate coefficients for the first three processes and found that excitation from metastable states and dissociative excitation is one to two orders of magnitude smaller than excitation rates from the ground state for electron temperatures larger than 2 eV.…”
Section: A Atomic Line Intensitysupporting
confidence: 90%
“…Nevertheless, several meaningful comparisons are possible: First, a few comparisons with recent lifetime data are available, which are shown in Tables 1 and 2. One group of lifetime measurements [8][9][10][11][12][13][14] ͑Table 1͒ is from levels which radiatively decay by LS-allowed, strong transitions to lower levels. These lifetime measurements have all been performed with laser-induced fluorescence techniques, i.e., selective excitation, and thus are expected to be quite accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Similar values have been observed for excited atoms of oxygen and other elements under conditions where the atoms and molecules can be expected to have a comparatively large translational energy. 11, 12 The fragments in the N0 2 dissociation can be expected to have a relatively high translational energy due to the excess energy of the X = 226 nm photon with respect to the onset for dissociation (X = 398 nm). The rapidly moving fragments will increase the collision frequency.…”
mentioning
confidence: 99%